Umbilical artery Doppler velocimetry in normal pregnancies from 11+0 to 13+6 gestational weeks: A Taiwanese study - Chia-Pei Chang; Hsing-I Wang; Peng-Hui Wang; Ming-Jie Yang; Chia-Ming Chang; Chi-Mou Juang; Yi-Jen Chen; Huann-Cheng Horng; Jen-Yu Tseng; Ming-Shyen Yen; Chih-Yao Chen; Kuan-Chong Chao (Elsevier, 2014)
Objective: The aim of this study is to investigate the relationship between umbilical artery flow and gestational age (GA) at 11-13+6 weeks in normal pregnancy in the Taiwanese population. Materials and methods: Two hundred and fifty-three normal singleton pregnancies with GA ranging from 11 to 13+6 weeks were included in this study. The velocity of systolic, diastolic, and pulsatility index (PI) of the umbilical artery, and the mean velocity of the umbilical vein were recorded. Results: One hundred and eighty-seven participants fulfilling the inclusion and exclusion criteria were analyzed. The mean maternal age was 31 (range 19-45) years, with a corresponding GA of 12+4 (range 11-13+6) weeks. The absence of end-diastolic velocity of the umbilical artery was observed in most of our cases (90.1%). No significant change was found in the vascular indices with GA for the mean velocity of the umbilical vein (mean velocity = 0.923 × GA − 1.594, r = 0.1497, p = 0.115). The systolic velocity of the umbilical artery and PI, however, behaved differently from the other variables. There was a significant increase in systolic velocity with GA [systolic wave (S wave) velocity = 0.237 × GA + 2.267; r = 0.149, p = 0.041]. By contrast, the PI showed a significant decrease in relation to the GA (PI = −0.016 × GA + 4.068; r = 0.196, p = 0.007). Conclusion: The S-wave velocity of the umbilical artery increased with GA. By contrast, the PI of the umbilical artery showed a decreasing trend with GA. This may ensure optimal placental perfusion, which is necessary to accommodate the increased blood flow to the developing fetus. Furthermore, an absence of end-diastolic velocity in the first trimester and early second trimester was usually seen.